Developing a Higher Order Thinking Skill-Oriented and Metacognitive-Based Assessment for Vocational School Students - Wening Patmi Rahayu; Uswatun Hasanah; Rully Wiliandri (Universitas Negeri Malang, 2020)
This study aims to provide an assessment instrument oriented to Higher-Order Thinking Skills (HOTS) based on metacognitive skill. The research product was analyzed for feasibility using a validation test of constructs and contents. The assessment instrument was measured with the difficulty and different levels of the questions. A valid product is tested to acknowledge the user's response. The results showed that the construct and content validation is valid, with 94 percent and 91 percent, respectively. The analysis of the different levels of the question showed a good different result. It implies that the instrument points lead to HOTS, which can improve students' metacognitive skills. The revised instrument was tested to the users, with the response was about 86.17 percent. The validation result from the experts and the response of the user can be concluded that the instrument of the HOTS-oriented and metacognitive-based assessment is entirely feasible, so it can be used as a guideline and reference by the teachers in the vocational school to develop similar products.